PERBEDAAN KEMAMPUAN MENULIS TEKS EKSPLANASI MENGGUNAKAN TEKNIK PEMBELAJARAN PETA KONSEP DENGAN MENGGUNAKAN TEKNIK PEMBELAJARAN KONVENSIONAL TERHADAP SISWA KELAS XI SMAN 1 ARGA MAKMUR KABUPATEN BENGKULU UTARA - Ervinda Eka Putri Agam (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2018)
The purpose of this research is to describe (1) the ability of student in XI IPA 4 SMAN 1Arga Makmur in 2016/2017 academic year in writing explanation text by using mind mapping technology, (2) the ability to write an explanation text by using a conventional technique in XI IPA 6 SMAN 1 Arga Makmur in 2016/2017 academic year, and (3) the difference of writing ability by using a mind mapping technology and conventional technology on students in XI IPA 4 and XI IPA 6 SMAN 1 ArgaMakmur. The technology of this research was a comparative causal with technique quantitative approach. The data of this research was the explanation text made by students in XI IPA 4 and XI IPA 6 SMAN 1 ArgaMakmur. The data was collected by conducting a writing test on student by writing explanation text based on instrument which has been validated by experts. The technique analysis of student writing ability was done by: 1) writing assessment, 2) prerequisit test, and 3) hypothesis test. The result of writing ability on explanation text by using mind mapping in XI IPA 4 was verry good with the average score was 83.While on the conventional class the average score of student in XI IPA 6 was only 76. The result of t-test hypothesist test was there is a significant different between the ability on student by using mind mapping technology and conventional technology. It showed by tcount > ttable which is, 7.59>1,68 with ? = 0,05. In care the conclution is Ho was rejected and H? was in accepted, so there is a significant different in ability on writing an explanation text by using a mind mapping technology an conventional technology.Keyword: Writing, Mind Mapping, Conventional, ExplanationText